Determinants of Hypovitaminosis D in Pregnant Women and Their Newborns in a Sunny Region. (1st July 2013) - Kelishadi, Roya; Sharifi-Ghazvini, Faezeh; Poursafa, Parinaz; Mehrabian, Ferdous; Farajian, Sanam; Yousefy, Hosseinali; Movahedian, Mahsa; Sharifi-Ghazvini, Sanaz
Abstract : Introduction. This study aims to assess the factors associated with 25-hydroxy vitamin D (25(OH)D) levels in pregnant women and their newborns in a sunny region. Materials and Methods. This cross-sectional study was conducted in 2012 in Isfahan, Iran. It comprised 100 nulliparous singleton pregnant women, selected by random cluster sampling. Laboratory tests were assessed before delivery in mothers and after delivery in their infants' umbilical cord blood. The P for trend of variables was assessed across the air quality index (AQI) quartiles. The associations of AQI and 25(OH)D were assessed by multiple linear regression after adjustment for age, body mass index, and dietary intake. Results. Sera of 98 mothers and an equal number of newborns were analyzed. The median (interquartile range, IQR) of serum 25(OH)D of mothers and neonates was 15.1(12.6, 18.2) ng/mL in mothers and 15.7(12.0, 18.1) ng/mL in neonates, respectively. AQI had an inverse association with serum 25(OH)D (Beta = −0.58, P = 0.04 ). The corresponding figure was also inverse and significant for newborns (Beta (SE)= −0.51(0.04), P = 0.01 ). Conclusion. The independent inverse association of 25(OH)D with air quality can explain the high prevalence of hypovitaminosis D in pregnant women living in this sunny region.